O Imposto Territorial Rural (ITR) no Brasil: uma nova proposta - Ribeiro, Daniel Oliveira (2023)
The Federal Constitution of Brazil provides for the possibility of entering into cooperation agreements regarding the Rural Territorial Tax – RTT and the sharing of tax revenue between the Union and Municipalities. For this study, a tax levied on rural properties was selected that affects all locations in the country, has extra-fiscal functions, is the responsibility of the Union and, over the years, has not materialized as an important source of public revenue in the country. In this context, the research problem is centered on the analysis of the collection of the RTT resulting from the perspective of municipal management through partnership of federative entities. Specifically, the objective is to evaluate the impact of the transfer of inspection and charge, the factors influencing the collection, and bring a comparison between the Brazilian regions, with emphasis on the Midwest region. The methodological procedures use descriptive research, correlation of static and dynamic variables, hypothesis tests and multi-regional analyses. It discusses the regulatory history of the tax, factors of formation of the country and structuring of land inspection and cooperation of federative entities. The results show an asymmetry of regional trends in adherence to RTT agréments and demonstrate the existence of connections between territorial extension, property pricing, tax administration structuring and effective collection results. It presents a training proposal for municipal public managers, brings as an alternative for future studies a tax reform with a re-discussion of the participation of States. Finally, the budgetary and environmental importance of the rural land tax is highlighted.